Pengaruh Media Komik Terhadap Peningkatan Hasil Belajar Siswa Sekolah Dasar 2 Alasangker, Buleleng, Bali - Kadek Jaya Sumanggala (Mahesa Research Center, 2023)
This study aims to determine the influence of Gautama Buddha's history comic media on learning outcomes of Elementary School 2 Alasangker. The method used in this research is quantitative research with experimental design. The instruments used in this research were questionnaires and evaluations which were distributed to 30 religious Buddhist students. The data obtained were then analyzed using a Likert scale and tested using the t-test. The results of this study indicate that comics have a very strong influence on, attractiveness, interest, motivation and understanding of learning each with an increase in learning outcomes, when viewed from the percent achievement of 88.33%, 89.16%, 77.50%, 88 ,66% (benefit). 85.83%. 93.33%, 80.83%, 74.16% (attractiveness). 86.66%. 78.33%, 71.66%, 80.00% (interest). 80.83%. 56.66%, 71.66%, 70.83% (motivation). 75.00%. 91.66%, 76.66%, 95.83% (understanding). From the results of the calculation of the comic media questionnaire with an increase in learning outcomes in total, the percentage of achievement is 80.58%. Furthermore, based on the t-test results from the evaluation of the learning achievement of Gautama Buddha's History material, it turns out that the media has a great influence on increasing learning outcomes. So, students are expected to learn well through the media used in the learning process so that they can improve their learning outcomes.